Sosialisasi Kewirausahaan Kerupuk Tempe dalam Meningkatkan UMKMMasyarakat di Desa Karang Gading - Helmi Salman Faris; Ade Nurul Wahyuni; Shalsha Billa Risky; Sahrul Affan (peduli riset dan pengabdian masyarakat, 2024)
The tempe cracker entrepreneurship seminar is an effort to educate the public in improving the SMEs of the Karang Gading village community. The tempeh cracker business is a business that can promise big business opportunities for the community because tempeh crackers are very popular with the Indonesian people, from children, adults, to the elderly. Tempe crackers are usually used as a meal companion or snack. The aim of this program is to improve the SMEs of Karang Gading village and encourage family economic income through the tempe cracker business.